A spatially distributed risk screening tool to assess climate and land use change impacts on water-related ecosystem services. (September 2016) - Sample, James E.; Baber, Ingrid; Badger, Rebecca
Abstract: To support the implementation of the European Water Framework Directive (WFD), and as part of a tiered approach to prioritise detailed modelling, a high-level screening methodology has been developed to assess the vulnerability of water-related ecosystem services (ES) to future change. The approach incorporates a range of spatially distributed scenarios of land use and climate, which are used as inputs to a qualitative risk assessment model underpinned by expert opinion. The method makes use of widely available datasets and provides a structured way of capturing and "codifying" expert knowledge, as well as for assessing the degree of consensus between different expert groups. The range of model output reflects uncertainty in both the expert-derived assumptions and the climate & land use simulations considered. The approach has been developed in collaboration with the Scottish Environment Protection Agency (SEPA) and applied in Scotland to support the second cycle of River Basin Management Planning. Highlights: We develop a transparent, structured methodology for capturing expert opinion. Estimated impacts include uncertainty in both future simulations and expert consensus. We consider 12 ecosystem services, 23 scenario combinations and more than 3000 catchments. Results have informed Scotland's second cycle of River Basin Management Planning.